Odjeci hrvatske kulture u djelu A. S. Puškina - Medarić, Magdalena (Array, 1999)
There are several articles dealing with Pushkin's relationship towards Southern slavs, and more specifically, towards Serbs. This article attempts to throw light on the question what Pushkin's knowledge of Croatian culure was, and whether it was possibily reflected in his oeuvre. It discusses the subject on three levels: level of personal acquintances: level of his scholarly sources; level of his artistic achievements. Tje last one turns out to be the most fruitful. Pushkin's poetical cycle Songs of Western Slavs depends upon ruch substratum in Croatian oral and verbal curtural tradition via Merimee's study of Morlaquism, but also via Pushkin's knowledge of other sources, such as Albert Fortis Journy in Dalmatia (1774.) and several others. The article also attempts at demystification of some V. Karadzic's songs incorporated in Pushkin's cycle, which are unadequatelly attributed in articles on Pushkin.